Pola Interaksi Pengguna Twitter Pada Akun Menfess @Areajulid - Linda Silviana; Yanti Tayo; Wahyu Utamidewi (Jurnal Ilmiah Wahana Pendidikan, 2022)
The emergence of the internet is a means of communication that makes it easier for us to communicate and interact with other users. The rise of the internet has led to the emergence of a form of communication in a medium with technology (Computer Mediated Communication). The purpose of this study is to describe how the interaction patterns carried out by twitter users who follow the menfess @areajulid account. This research is a qualitative research using Virtual Ethnography method. The results of the study found that the type of twitter user interaction pattern is a dissociative interaction pattern where this interaction pattern is an interaction process that leads to disputes between individuals and groups to achieve certain goals. In this study, dissociative interaction patterns are included in the type of social conflict where conflict is a tension that occurs between individuals or groups to cause a conflict.